Euphorbiaceae novae vel criticae colombianae, iv (1944)
Croton Linnaeus / Croton palanostigma / Croton cearensis / Croton huitotorum / Croton Killipianus / Croton Smithianus / Croton chocoanus / Croton sibundoyensis / Croton boavitanus / Croton Purdiei / Croton polycarpus / Croton magdalenensis / Croton Mutisianus / Croton ater / Croton Lechleri / Croton gossypiifolius / Croton hibiscifolius.